Święcenie zwierząt w Mikstacie. Tradycja i współczesność - Zacharek, Natalia (Studia Etnologiczne i Antropologiczne, 2020)
This text focuses on comparing two images of the rite of the blessing of animals in Mikstat, based on 19th and 20th century literature, as well as on research from August 16, 2018. The analysis of old symbols, magical activities, and longforgotten celebrations is juxtaposed with contemporary changes in tradition which have created new symbolism for, and interest in, the older elements that comprise the cultural heritage of Mikstat. For at least 300 years, the purpose of the traditional rite of the blessing of animals on the Day of St. Roch (August 16) has been to preserve the health, happiness, and fertility of farm and livestock.